FRI0292 Children born to mothers with sle: no increase in males and hydroxychloroquine does not protect against neonatal lupus. (23rd January 2014) - Gayed, M.; Khamashta, M.; Culliford, D.; Leone, F.; Toescu, V.; Bruce, I.; Giles, I.; Teh, L.-S.; Mc Hugh, N.; Akil, M.; Edwards, C. J.; Gordon, C.
Abstract : Background: Recent Canadian data suggested an increased male:female ratio in children born to women with SLE 1 . However results combined from PROMISSE and RRNL data demonstrated no ignificant gender difference 2 but reported hydroxychloroquine(HCQ) was protective against cardiac neonatal lupus(NL) in subsequent pregnancies in mothers with anti-Ro/La antibodies and a prior child with cardiac-NL 3 Objectives: To address the following questions in UK cohort of children born to mothers with SLE: 1)Does HCQ protect against NL? 2)Is there an increased M:F ratio? Methods: A cross sectional, retrospective study recruited women with 4 SLE ACR criteria attending 8 specialist UK clinics with available pregnancy data for children under 17 yrs born after maternal SLE diagnosis. A standard questionnaire developed for multi-centre study was used to collect data on each pregnancy and the child outcome. Data collected included ethnicity, age of mother, disease duration, autoantibody profile, exposure to HCQ and immunosuppressive drugs during pregnancy/lactation, age and gender of child, and medical conditions assessed at a hospital in the child. Results: Complete data was available for 288 children born alive to 200 women: 66% Caucasian, 15% South Asian, 10% Afro-Caribbean, 1% Chinese, 1% Hispanic 4% other and 4% not stated. The median (range) age of women at delivery was 32 (19-44) yrs, and duration of disease was 6 (0-27) yrs. There were 128 (44%) male and 160 (56%) female children with M:F gender ratio of 0.80 (95% CI 0.63-1.01). In total 136 (47%) of children were exposed to HCQ and 152 (53%) were unexposed during pregnancy. Congenital heart block (CHB) was observed in 7 (2.5%) children and cutaneous NL was reported in 6 (2%) children. The frequency of CHB or cutaneous NL, was not significantly different in children exposed to HCQ versus those not exposed, OR 1.27 for all types of NL, 95%CI 0.39-4.08 (p=0.69). As expected the only significant risk factor associated with cardiac and cutaneous NL was anti-Ro±La antibodies, OR15.1, 95%CI 1.90-119.8 (p=0.01), which remained significant on multivariate analysis OR16.4 (p=0.01). There were no other significant potential risk or protective factors associated with cardiac or cutaneous NL; none of the other immunosuppressive drugs offered protection. Conclusions: Gender ratio was almost equal and consistent with PROMISSE and RRNL data, in contrast to previously published Canadian data. . In contrast to published registry data that HCQ may be protective against recurrence of cardiac NL in subsequent pregnancies, HCQ was not protective against CHB &/or cutaneous NL in this UK cross sectional study. References: Vinet et al. Increased M:F Ratio in Children Born to Women with SLE.A&R.2013. Letter.[Epub ahead of print] Lockshin et al. Sex ratios of children of lupus pregnancies.A&R.2013.65:282 Izmirly et al. Maternal use of HCQ is associated with a reduced risk of recurrent anti-Ro-antibody-associated cardiac manifestations of NL.Circulation.2012:126:76-82 Acknowledgements: Lupus UK Disclosure of Interest : None Declared